2022
DOI: 10.3390/ijms23084102
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Concepts and Dextrin-Based Delivery Systems

Abstract: Nutraceuticals are bioactive or chemical compounds acclaimed for their valuable biological activities and health-promoting effects. The global community is faced with many health concerns such as cancers, cardiovascular and neurodegenerative diseases, diabetes, arthritis, osteoporosis, etc. The effect of nutraceuticals is similar to pharmaceuticals, even though the term nutraceutical has no regulatory definition. The usage of nutraceuticals, to prevent and treat the aforementioned diseases, is limited by sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 339 publications
0
23
0
Order By: Relevance
“…One of the strategies in biomedicine to overcome these disadvantages is the use of nanostructures, such as nanocarriers. Thus, Hoti et al summarized nanotechnology-based delivery systems used for nutraceutical transportation [ 171 ]. Moreover, this group contextualized modified cyclodextrin (CD)-based nanosponges (NSs; CD-NSs) as efficient encapsulating agents for delivering nutraceuticals with controlled kinetics through the topical, oral, and parenteral routes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strategies in biomedicine to overcome these disadvantages is the use of nanostructures, such as nanocarriers. Thus, Hoti et al summarized nanotechnology-based delivery systems used for nutraceutical transportation [ 171 ]. Moreover, this group contextualized modified cyclodextrin (CD)-based nanosponges (NSs; CD-NSs) as efficient encapsulating agents for delivering nutraceuticals with controlled kinetics through the topical, oral, and parenteral routes.…”
Section: Resultsmentioning
confidence: 99%
“…CD-NSs are the most preferred, advanced, biocompatible, and natural systems to deliver nutraceuticals. These nanocarriers are used as delivery systems of several nutraceuticals, such as quercetin, curcumin, and resveratrol [ 171 ]. Soni et al demonstrated that SFN-loaded nanostructured lipid carriers (NLCs) improve oral efficacy against cancer.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the demand for health care has intensively increased, and the attention of people has focused on the requirement for foods enriched with nutraceuticals to obtain adequate nutrients that allow both to maintain the normal functioning of the body and to prevent disease. Based on experimental studies, the therapeutic purpose of nutraceuticals depends on their bioavailability, solubility, toxicity, and delivery system [ 117 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Recent studies have demonstrated that dextrins can be used in the nutraceuticals delivery industry because of their non-toxic, biodegradable, and water solubility characteristics [ 117 , 118 ]. Dextrins—derived from starch—are considered an effective drug delivery tool with proven clinical tolerability [ 119 ], and the dextrin polymer-based nanocarriers are designed to be the preferred and natural system for providing nutraceuticals.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Nutraceuticals are “unstoppable” in the global market despite the brevity of experts’ definitions of what they are (Figure ). The global nutraceutical market evokes continuous controversy, so it is essential to evaluate it. The nutraceuticals industry is divided into functional foods, natural or herbal products, and dietary supplements .…”
Section: Global Market Of Nutraceuticalsmentioning
confidence: 99%